The relationship between self-efficacy, illness-related fear, and intolerance of uncertainty in patients who have epilepsy in eastern Turkiye: A path analysis - Erden, Yasemin; Turan, Gulcan Bahcecioglu; Karakurt, Nurgul; Bakir, Ercan (Academic Press Inc Elsevier Science, 2025)
Background: The effects of psychological factors such as self-efficacy, illness-related fear, and intolerance of uncertainty on illness management and quality of life of patients who have epilepsy have important roles in understanding the health behaviors of individuals. Aim: The present study was conducted to examine the relationship between self-efficacy, illness-related fear, and intolerance of uncertainty in patients who have epilepsy and to investigate the mediating role of illness-related fear in the relationship between self-efficacy and intolerance of uncertainty. Method: This cross-sectional and correlational study had a descriptive design and was conducted with 150 epilepsy patients who met the inclusion criteria and applied to the neurology clinic of a university hospital. The study population comprised epilepsy patients who applied to the Neurology Clinic of a university hospital in eastern Turkiye between May 2024 and August 2024. The data were collected by using the Personal Information Form, Epilepsy Self-Efficacy Scale, Illness-Related Fear Scale, and Mishel Uncertainty in Illness Scale - Community Form. The Structural Equation Modeling and Bootstrapping Methods were used to analyze the study data. The study was reported following the STROBE Recommendations. Results: Based on the findings, self-efficacy was found to negatively affect intolerance of uncertainty about the illness (b = -0.384, 95 % CI [-0.462 to -0.306], p < 0.01) and illness-related fear (b = -0.449, 95 % CI [-0.544 to -0.344], p < 0.01). Also, illness-related fear was found to positively affect intolerance of uncertainty (b = 0.688, 95 % CI [0.586 to 0.789], p < 0.01). The indirect effect of self-efficacy on intolerance of uncertainty through illness-related fear (b = -0.309, 95 % CI [-0.444 to -0.210], p < 0.01) was found to be negative and significant and the total effect (b = -0.693, 95 % CI [-0.789 to -0.597], p < 0.01) was also negative and significant. Self-efficacy explained 34 % of the illness-related fear and 59 % of the total intolerance of uncertainty in the model. The estimated effects were calculated with 5000 repeated operations and were evaluated to be significant because the indirect effects did not include zero in the 95 % Confidence Interval. Conclusion: The results of the present study showed that self-efficacy has a direct negative impact on intolerance of uncertainty in patients who have epilepsy and that fear related to the illness plays mediating roles in this effect.
Keywords: Epilepsy; Self-efficacy; Intolerance of uncertainty; Fear